Episiotomy practices and associated factors in central Vietnam - Hoang Thi Nam Giang; Do Thi Thuy Duy; Thanh-Huyen T. Vu (PLoS ONE, 2026)
Introduction Research on episiotomy practices in Vietnam is limited. This study aimed to describe episiotomy use and identify factors associated with its practice among vaginal births in Central Vietnam, following the implementation of restrictive episiotomy guidelines. Methods We used data from a hospital-based, retrospective study conducted at Danang Hospital for Women and Children from April 2015 to March 2016. The study included all singleton, full-term vaginal births. Multivariable logistic regression was used to estimate the odds of episiotomy based on selected neonatal or maternal factors. Results Among 3,471 eligible singleton births, 2,770 mothers (79.8%, 95% CI: 78.4% − 81.1%) underwent an episiotomy. The episiotomy rate was significantly higher in first-time births (97.7%, 95% CI: 96.8% − 98.3%) compared to second or subsequent births (61.5%, 95% CI: 59.2% − 63.8%), p < 0.001. Multivariable analyses showed that first-time births, higher birth weight, younger maternal age, a less physical active occupation, and a history of miscarriage were significantly associated with higher odds of episiotomy. For example, the odds of episiotomy in first-time births was 24.21 (95% confidence interval (CI): 17.13 – 34.22) times higher than in second or subsequent births, and the odds for mothers with a history of miscarriage was 1.34 (95% CI: 1.03 – 1.73) compared to those without. Stratified analysis showed that these associations persisted in multiparous women but were not observed in primiparous women. Conclusion This study highlights a very high episiotomy rate in Central Vietnam, especially among primiparous women despite recommendations from the World Health Organization and the Vietnam Ministry of Health. Several modifiable maternal and neonatal factors are linked to episiotomy use in multiparous women. While one year may not be sufficient to fully assess the restrictive policy’s effect, the results of our study also suggest that the policy has not had a significant impact on reducing the episiotomy rate after one year. This indicates that, in addition to the policy, further support and interventions are needed to reduce episiotomy rate.